Analyzing Psychotherapeutic Failures: A Research on the Variables Involved in the Treatment With an Individual Setting of 29 Cases - Maggio, Simone; Molgora, Sara; Oasi, Osmano (Frontiers in Psychology, 2019)
The effectiveness of psychotherapeutic treatments has been widely demonstrated and confirmed by many studies in recent decades. The research focused on the factors of change influencing the positive outcomes of a psychotherapy, putting those that are crucial in cases of failure into the background. The dimensions of this phenomenon are relevant as well as the side effects of the psychotherapeutic interventions that reach the same percentages of the pharmacotherapeutic treatments. The study of the variables involved in failure cases therefore seems important to prevent or moderate the negative effects of treatments with a negative outcome. Impasse and deadlock situations, which may result in an early interruption of psychotherapy, are often complex and involve situational, relational and personal factors at different levels and with different weight. A research was conducted, with a mixed approach, aimed at exploring the situational factors involved in dropout cases. In addition, the evaluation of the psychotherapist's emotional responses related to patients who terminated psychotherapy prematurely was investigated. The study was attended by a sample of 29 psychologists, experienced psychotherapists from different frameworks. Recent or salient cases of a hesitated psychotherapy with an early interruption were examined. For the first objective, a structured interview (Impasse Interview) was used, while the second one was reached by the administration of the TRQ (Therapist Response Questionnaire). The transcripts of the interviews were analyzed through a textual analysis software and 5 salient thematic clusters were identified. These were then assimilated to different areas of meaning: severity of the diagnosis, procedural aspects and lack of understanding of the stall in progress. Two other important themes emerged: the critical aspects concerning relational dynamics and a focus on maternal theme. Overall these 5 thematic areas seem to play an important and specific role compared to dropout cases. Finally, statistical analysis on emotional responses have highlighted some values above the average in these 4 countertransference factors: Helpless / inadequate, Parental / protective, Positive / satisfied and Overwhelmed / disorganized. It is hypothesized that particular emotional responses of the psychotherapist may be prognostic with respect to the outcome of psychotherapy.